Pemberdayaan Komunitas Melalui Asuhan Kebidanan untuk Mengurangi Kasus Diare di Desa Pemepek Pringgarata - Andriani, Ni Wayan Lilik wiri; Apriani, Lia Arian (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Diarrhea remains a major cause of morbidity and mortality in children under five worldwide, with more than 1.7 billion cases each year and around 525,000 deaths, according to WHO. Indonesia, including West Nusa Tenggara, has a high prevalence of diarrhea due to limited sanitation and access to clean water. The Pringgarata area, Central Lombok Regency, recorded 250 cases of diarrhea in children in the first six months of 2023, triggered by low public awareness of Clean and Healthy Living Behavior (PHBS). This community service activity aims to increase the knowledge of mothers of toddlers about the causes, prevention, and treatment of diarrhea through leaflet-based counseling. The method used is counseling with an interactive approach including three stages: preparation, implementation, and evaluation. The counseling began with a pre-test to measure initial knowledge, followed by the delivery of material using leaflets, and ended with a post-test and question and answer session. A total of 15 participants took part in the activity, with the pre-test results showing that only 26.6% of participants had basic knowledge. After the counseling, this figure increased significantly to 93.3%. The results showed that the use of leaflet media and interactive methods significantly increased participants' understanding. This community-based counseling is effective as a health promotion effort in preventing diarrhea. As a suggestion, similar programs can be replicated in other areas, accompanied by cross-sector collaboration to strengthen public health education and the provision of sanitation facilities and clean water. Increasing public awareness is expected to reduce the incidence of diarrhea and support the national target in reducing the prevalence of stunting.